A STUDY ON ASSOCIATION OF SYSTOLIC BLOOD PRESSURE, DIASTOLIC BLOOD PRESSURE, AND PULSE PRESSURE WITH INTRAOCULAR PRESSURE IN RELATION TO PRIMARY OPEN-ANGLE GLAUCOMA - Roy, Sudeshna; Chatterjee, Arkendu; Ghanta, Debalina; SHAMIN AHAMED (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study aims to probe the relationship among pulse pressure (PP), systolic blood pressure (SBP) and diastolic blood pressure (DBP), and the intraocular pressure (IOP) in normal persons and primary open-angle glaucoma (POAG) patients. Design: This was an institution-based observational study. Methods: This study was conducted on 240 patients attending the ophthalmology department and glaucoma clinic of a tertiary hospital. Included subjects were asked about their ocular and systemic problems and undergone detailed examination of eyelids, conjunctiva, cornea, anterior chamber by slit lamp, visual acuity, refraction, and fundus examination. IOP was measured by Goldmann applanation tonometer. Blood pressure was measured by sphygmomanometer. Results: In this study, we found that SBP, DBP, PP, and IOP – both eyes were found to be higher in subjects with POAG than normal control subjects. Among these, differences in mean SBP, DBP, and IOP – both eyes between subjects with POAG and normal subjects were statistically significant. IOP was found to be positively correlated with SBP, DBP, and PP both in subjects with POAG as well as in normal subjects. Conclusion: Although involving a limited number of eyes, the key findings of the study suggest that IOP is positively correlated with PP, SBP, and DBP. This opens up the possibility of early detection of glaucoma patients with raised PP, SBP, and DBP.